Transmission electron microscopy and atom probe specimen preparation from mechanically alloyed powder using the focused ion-beam lift-out technique - Choi, Pyuck-Pa; Kwon, Young-Soon; Kim, Ji-Soon; Al-Kassab, Tala'at (OXFORD UNIV PRESS, 2007)
The preparation of transmission electron microscopy (TEM) and atom probe-field ion microscopy (AP-FIM) specimens from mechanically alloyed Ti-Cu-Ni-Sn powder has been explored. Applying the focused ion beam (FIB) based in situ lift-out technique, it has been demonstrated that specimen preparation can be carried on single micrometre-sized powder particles without the use of any embedding media. Since the particles did not incorporate any micropores, as revealed by cross-sectioning, the standard procedure known for bulk samples could be simply implemented to the powder material. A sequence of rectangular cuts and annular milling was found to be a highly efficient way of forming a tip-shaped AP-FIM specimen from a square cross-section blank. A Ga level <= 1 at.% was detected if a low beam current of 10 pA was chosen for the final ion-milling stages. Implanted Ga ions were mostly confined to a zone of about 2 nm in thickness and indicated that ion-induced structural transformations were negligible.
Keywords: BULK AMORPHOUS-ALLOYS; FILM STRUCTURES; TEM; FIB; EXTRUSION; SEM